Implementación de un sistema de costos por procesos en la microempresa lácteos la libertad, ubicada en la parroquia Mulaló, cantón Latacunga, provincia Cotopaxi para el periodo 2014 - Quinatoa Toaquiza, María Margarita (2015)
The objective of this research is to implement a process costing system in the Milky enterprise “LA LIBERTAD”, for it was determined that the main problem affecting the production is the lack of a cost system; therefore it did not allow him to know precisely the actual cost of production because the product price is calculated empirically. By implementing this system will establish the costs of raw materials, labor and manufacturing overhead costs thus obtaining the actual cost of the product as well as the financial statements used for decision making. The research in this paper is not experimental the methods used are: inductive, deductive, analytical and systematic. Furthermore, techniques such as interviews and survey its instrument the same as those applied to the owner, employees, suppliers and customers, allowing that information to the realization of this research is collected. In conclusion, the implementation of a cost system for processes in the Milky enterprise “LA LIBERTAD”, helped to determine the exact costs invested in each production process by optimizing the three elements of cost in order to improve profitability.